Frequency Analysis of Blasting Data - Stephen A. Rholl (International Society of Explosives Engineers, 1996)
Computer software has been developed which uses fast Fourier Transform (FFT) techniques to analyze the frequency spectrum associated with peaks in ground vibration time histories. The procedure consists of filtering the FFT of a time history into individual frequency components.